DIVINE REVELATION AS THE SOURCE OF DIALOGUE AMONG RELIGIOUS FORMS (Religious dialogue and cooperation, 2023)
Divine Revelation is rarely considered in its all-embracing importance. We findmore often particularistic interpretations defined by certain traditions, confessions, andtheoretical schools rooted in a certain historical period. Such approaches are valuablecontributions as they offer a possible way to understand the world in a more-than-trivialfashion. Philosophical and theological developments based on particularistic traditionsare also helpful because they show the power of genuine inspiration. Nevertheless, theproblem of divine revelation cannot be confined to a particular tradition. The concept ofrevelation suggests that revelation as a basic concept rises above historical, cultural, anddenominational forms and elevates human persons to a sphere where divine reality disclosesan overarching design. In today’s world, where various traditions, religious forms,and denominations are becoming interconnected, it is essential to understand divine revelationin a way that is not distorted by various particularisms. In a few published works,I have repeatedly pointed out the essential feature of divine revelation as unrestrictednewness. In the following text, I will argue that this newness comes to the fore as soon aswe perceive revelation properly. Focusing on newness, we can reconsider particular narrativesof divine revelation from the perspective of their renewing power leading to a globalcommunity of human beings. To achieve this, I emphasize the importance of spiritualpractice, such as revelatory meditation, through which people of various backgroundscan think through their understandings of divine revelation. By doing so, we can open thepossibility of finding a common theoretical praxis to mend the world.
Keywords: Divine Revelation; natural revelation; radical revelation; comparative religion